Communicating public and social services through iTV: Promoting older adults’ quality of life - Campelo, David (2018)
As the demographic transition occurs in a global scale, dealing with the consequences of population ageing has emerged as a critical task to modern societies. This has led government entities to pay more and more attention to seniors’ concerns, limitations and needs. A deep understand of old citizens, especially those unfamiliar with Internet and smartphone technologies, is also a challenge in order to enable them to fully benefit of the Information and Communication Technologies (ICTs). In the light of this issue, personalization and user-centred approaches involving older adults in all development stages may be the key for higher levels of user engagement with such ICT solutions as the interactive television (iTV) platform reported in this paper (+TV4E). The +TV4E is an on-going research project conducted at University of Aveiro, Portugal, based on a social inclusion approach, aiming to take benefit from the television viewing dynamics of senior viewers, by interweaving short and personalized adverts related to public and social services alongside regular broadcast contents. The platform is being designed with a user-centred approach featuring the integration of assistive technologies and multiple multimedia communication channels. In this paper, a system architecture to deliver the informative contents is stated and a discussion of the potential social impacts of providing such platform is presented.